Scoliosis and Bronchial Obstruction - Mehdi Qiabi; Karine Chagnon; Alain Beaupré; Julian Hercun; George Rakovich (Canadian Respiratory Journal)
Severe scoliosis may have a significant effect on respiratory function. The effect is most often restrictive due to severe anatomical distortion of the chest, leading to reduced lung volumes, limited diaphragmatic excursion and chest wall muscle inefficiency. Bronchial compression by the deformed spine may also occur but is more unusual. Management options include a conservative approach using bracing and physiotherapy in mild cases, as well as surgical correction of the scoliosis in more severe cases. Bronchial stenting has also been used successfully as an alternative to surgical correction, and in cases in which spinal surgery was either unsuccessful or not feasible. The authors present a case involving a 52-year-old woman who exhibited symptomatic compression of the bronchus intermedius by severe residual scoliosis despite previous corrective surgery. She was treated with an indwelling bronchial stent.